A web presence analysis of Malaysian government agency websites - Osman, Baharudin; Abas, Azizi; Idrus, Mohd Rushdi; Sarkawi, Azizah (Faculty of Information Technology, Universiti Utara Malaysia, 2006)
The focus of this research is to identify the Malaysian government web presence stage,quality factors based on the last update period and downloading time and the website upadating problem from webmaster view the study employed a multi-method approach such as inspection method on selected websites. URL analyse using web diagnoslic tools and e-mail survey. An analysis of 74 government agencies website shows that the majority of Malaysian government website did not achieves the expected quality with only 31 percent which has been updated less than once a month and 76 percent are poor in downloading times (more than 10 seconds).